Storage of onion bulbs under different intermittent air flows - Teixeira de Matos, Antonio; Antoninho Dalpasquale, Valdecir; Luiz Finger, Fernando (Pesquisa Agropecuaria Brasileira, 1998)
Onion bulbs were stored in 0.56 m diameter x 2.15 m height silos as bulk in 2.0 m height layer of bulbs under intermittent air flows of 0.5, 1.0 and 1.5 m3.min-1.m-3. Bulbs were stored during three months, receiving daily periods of aeration, whose length was determined by the exhaustion air psychrometric conditions. The flow rates and the period of storage tested did not affect the bulbs humidity content; however, the flow of 0.5 m3.min-1.m-3 induced an increase in the skin humidity after 60 days of storage. Air flow of 0.5 m3.min-1.m-3 was insufficient to allow over 60 days storage period, however flows of 1.0 and 1.5 m3.min-1.m-3 decreased the percentage of bulb deterioration and prolonged the postharvest life when compared to the lower flow rate. Under the two higher flow rate, total mass lost was 20.7% after 88 days of storage.